Deconfinement and chiral phase transitions in quark matter with chiral imbalance - Azeredo, Francisco X.; Duarte, Dyana C.; Farias, Ricardo L.S.; Krein, Gastão [UNESP]; Ramos, Rudnei O. (American Physical Society (APS), 2024)
We study the thermodynamics of the Polyakov-Nambu-Jona-Lasinio model considering the effects of an effective chiral chemical potential. We offer a new parametrization of the Polyakov-loop potential depending on temperature and the chiral chemical potential which, when used together with a proper regularization scheme of vacuum contributions, predicts results consistent with those from lattice simulations.